Reading Robert Greene recovering Shakespeare's rival - Freebury-Jones, Darren (Routledge, Taylor & Francis Group, 2022)
Situating Greene -- Defining Greene -- Greene's acknowledged plays -- Collaborating with Greene -- Greene's marginal plays -- Comparing Greene's marginal plays -- Recovering Greene
Includes bibliographical references and index
Keywords: Greene, Robert -- 1558-1592; Greene, Robert / 1558-1592 / Literary style; Greene, Robert / 1558-1592 / Criticism and interpretation; English drama / Early modern and Elizabethan, 1500-1600 / History and criticism